Integration of AI Deep Learning in Studying the Morphology of Philosophy of Science Perspectives - adhia nugraha; Rohanda Rohanda; Abdul Kodir; R. Edi Komarudin (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
This article aims to make a significant contribution to the understanding of artificial intelligence (AI) in the context of morphology and the philosophy of science, while emphasizing the importance of interdisciplinary and innovative approaches in future research. The study discusses the integration of deep learning-based AI in morphological studies from a philosophical perspective. The authors present an innovative approach that connects modern AI technology with philosophical paradigms to enhance the understanding of morphology. Through literature analysis and case studies on Arabic quotes, the authors demonstrate that deep learning AI models can significantly improve the accuracy and efficiency of morphological analysis. The philosophical approach developed in this article provides an epistemological context for AI analysis results, highlighting its ontological aspects. The implications of this research include the potential for collaboration among different disciplines and recommendations for future research on the integration of AI and the philosophy of science.